2019
DOI: 10.1111/aogs.13573
|View full text |Cite
|
Sign up to set email alerts
|

Elective egg freezing without medical indications

Abstract: The aim of this review is to provide current knowledge on fertility preservation for non‐medical reasons in women willing to postpone childbearing. The topic is highly debatable, starting from disagreement about its terminology, the number of eggs necessary to predict chances of success, and the safety and socio/ethical point of view. Cost analysis and discrepancies among countries’ recommendations and regulations are described to confirm the controversies and unsolved issues around this very interesting topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 51 publications
(121 reference statements)
1
30
0
Order By: Relevance
“…The cost of freezing eggs is significant, with recurring annual storage costs, and it is a clear deterrent to women who are considering OFNMR. Ikhena‐Abel et al illustrated that financial reimbursement, as already offered by some companies, 54 would promote consideration of OFNMR among some women in the general public and was not viewed as coercive 19 . Companies such as Apple, Facebook, and Google offer subsidized freezing for some staff.…”
Section: Discussionmentioning
confidence: 99%
“…The cost of freezing eggs is significant, with recurring annual storage costs, and it is a clear deterrent to women who are considering OFNMR. Ikhena‐Abel et al illustrated that financial reimbursement, as already offered by some companies, 54 would promote consideration of OFNMR among some women in the general public and was not viewed as coercive 19 . Companies such as Apple, Facebook, and Google offer subsidized freezing for some staff.…”
Section: Discussionmentioning
confidence: 99%
“…Due to postponement of childbearing, low ovarian reserve has become an important matter in female infertility (Ubaldi et al, 2019). The growing number of fertility preservation cycles performed for social reasons in IVF clinics in developed countries signals the success of the efforts made to communicate the effects of female age on oocyte quality and ovarian reserve (Alteri et al, 2019). However, a significant portion of the population still cannot afford ART procedures.…”
Section: Topic Frequencymentioning
confidence: 99%
“…The chance of having the desired outcomes such as high oocyte survival and live birth rates depend on womens’ age,13 the number of retrieved mature oocytes14 and the number of frozen eggs 13. Previous studies’ report lack agreement regarding the optimal timing of oocyte cryopreservation 9 14 15. One study showed the live birth rate was higher among women aged ≤35 years compared the older women (>35 years) 14.…”
Section: Introductionmentioning
confidence: 99%